Increasing grain yield potential and stability in durum winter wheat in Ukraine - Palamarchuk, A.I. (Фактори експериментальної еволюції організмів, 2014)
Aims. To test different features of yield structure and adaptive qualities of durum winter wheat varieties this influenced on significant rise of yield potential and stability. Methods. The first varieties of typical winter durum wheat were created by interspecies hybridization varieties of bread winter and durum spring wheat, following by saturated crosses with bread winter wheat. Results. Introgression into genotype of extensive varieties of durum winter wheat genes of dwarfness and alleles of low photoperiodic sensitivity resulted by grain yield rising on 1.8 t/ha compare to previous varieties exchange. These modifications become possible because of redistribution of plastic matters during ontogenesis to grain part, as yield index showed. Productivity increasing of varieties of durum winter wheat was dependent on rising of biomass (+0.62 kg/m²), at first. Conclusions. Increasing of potential productivity and stability of grain yield of durum winter wheat can’t be achieved without high adaptability to a biotical and biotical factors of stress environment.

Key words: durum winter wheat, yield potential, varieties, adaptability.